THE EFFECT OF SUPERVISORS' SOCIAL SUPPORT AND SELF-EFFICACY ON ANXIETY IN STUDENTS WHO ARE PREPARING THEIR THESIS AT MALAHAYATI UNIVERSITY - Dewita Cahaya Saqina; Asri Mutiara Putri; Dary Ies Shabrina (Yayasan Multidimensi Kreatif, 2026)
This study aims to determine the influence of supervisors' social support and self-efficacy on academic anxiety in students who are preparing their thesis at Malahayati University. This study uses a quantitative approach with a research sample of 137 students. Data were collected through the academic anxiety scale, the supervisor's social support scale, and the self-efficacy scale which was compiled in the form of a questionnaire with the Likert scale. Data analysis was carried out using multiple linear regression with the help of the SPSS program. The results of the study showed that simultaneously the social support of the supervisor and self-efficacy had a significant effect on academic anxiety by 50.4% Partially, the social support of the supervisor did not have a significant effect on academic anxiety, while self-efficacy had a significant effect on academic anxiety. These findings show that self-efficacy is a more dominant factor in influencing academic anxiety in students who are preparing their thesis and plays an important role in helping students face academic demands during the study completion process.